Transcriptomic analysis reveals cloquintocet-mexyl-inducible genes in hexaploid wheat (Triticum aestivum L.) - Olivia A. Landau; Brendan V. Jamison; Dean E. Riechers (PLoS ONE, 2025)
Identification and characterization of genes encoding herbicide-detoxifying enzymes is lacking in allohexaploid wheat (Triticum aestivum L.). Gene expression is frequently induced by herbicide safeners and implies the encoded enzymes serve a role in herbicide metabolism and detoxification. Cloquintocet-mexyl (CM) is a safener commonly utilized with halauxifen-methyl (HM), a synthetic auxin herbicide whose phytotoxic form is halauxifen acid (HA). Our first objective was to identify candidate HA-detoxifying genes via RNA-Seq by comparing untreated and CM-treated leaf tissue. On average, 81% of RNA-Seq library reads mapped uniquely to the reference genome and 76.4% of reads were mapped to a gene. Among the 103 significant differentially expressed genes (DEGs), functional annotations indicate the majority of DEGs encode proteins associated with herbicide or xenobiotic metabolism. This finding was further corroborated by gene ontology (GO) enrichment analysis, where several genes were assigned GO terms indicating oxidoreductase activity (34 genes) and transferase activity (45 genes). One of the significant DEGs is a member of the CYP81A subfamily of cytochrome P450s (CYPs; denoted as CYP81A-5A), which are of interest due to their ability to catalyze synthetic auxin detoxification. To investigate CYP expression induced by HM and/or CM, our second objective was to measure gene-specific expression of CYP81A-5A and its homoeologs (CYP81A-5B and CYP81A-5D) in untreated leaf tissue and leaf tissue treated with CM and HM over time using RT-qPCR. Relative to the reference gene (β-tubulin), basal CYP expression is high, expression among these CYPs varies over time, and expression for all CYPs is CM-inducible but not HM-inducible. Further analysis of CYP81A-5A, such as gene knock-out, overexpression experiments, or in vitro activity assays with purified enzyme are necessary to test the hypotheses that the encoded CYP detoxifies HA and that CM upregulates this reaction.